Choreographic Form of Gregah Dance by Ambarwati in Kediri City - Pramesthi Murganingrum, Kharisma (Solah, 2025)
Gregah dance was created by Ambarwati in 2015, in order to take part in the East Java Regional Dance Festival organized by the East Java Province Cultural Tourism Office. The meaning of the word ‘Gregah’ or ‘Gumregah’ is to rise. The movement visualization presented in this dance means the tenacity and enthusiasm of women in carrying out their roles and responsibilities. The uniqueness of this dance is that it depicts the strength that exists in a woman's feminism. There has never been any previous research examining this dance work. The interesting choreography makes researchers want to analyze this dance more deeply through studying the choreographic form. The formulation of the research problem is (1) what is the background to the creation of Ambarwati’s Gregah Dance in Kediri City and (2) what is the choreography of Ambarwati’s Gregah Ddance in Kediri City. The aims of the research are (1) to describe the background to the creation of Ambarwati’s Gregah Dance in Kediri City and (2) to describe the choreography theory. The theory used to study is the theory of choreography by Sumandiyo Hadi, which explains that choreography includes all the elements that make up a dance work. The research method used is descriptive qualitative with data collection techniques through observation, interviews and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The research results show that choreographically, Gregah dance arranged in harmony through a combination of supporting elements of the dance form including: movement patterns and techniques based on local traditional movements, dance music, make up design and dance clothing. All of these elements are integrated to produce a distinctive and characteristic dance style that expresses the life values of women who have a high enthusiasm for life. Apart from that, choreography Gregah dance it also looks dynamic with the arrangement of forms taking into account the principles of beautiful choreographic form.